THE KONDAROS-KATSIMOUTI INTERMEDIATESULFIDATION EPITHERMAL PB-ZN-AG-MN MINERALIZATION, WESTERN MILOS, GREECE: NEW MINERALOGICAL AND GEOCHEMICAL DATA - Papavasiliou, K.; Voudouris, P.; Kanellopoulos, C.; Alfieris, D.; Xydous, S. (Bulletin of the Geological Society of Greece, 2016)
The metallic mineralization in Kontaros-Katsimouti area is an epithermal Pb-Zn Ag mineralization located along the NW-trending Kondaros-Katsimouti-Vani fault, NW Milos Island, Greece. It is hosted within propylitically and argillically altered dacitic flow dome and volcaniclastic sandstone and shows features typical of intermediate sulfidation deposits like colloform banding, cockade breccias and gangue adularia, Mnrich carbonates and amethystine quartz. The Kondaros-Katsimouti system evolves at higher elevation into the Vani Ag-Pb mineralization, which occurs proximal to the Vani manganese deposit. The metallic mineralogical assemblage at Kondaros-Katsimouti includes mainly galena and sphalerite and minor pyrite. Silver is present in the form of Ag-(Cd) rich tetrahedrite (up to 23.1 wt. % Ag) and polybasite included in galena. Bulk ore analyses indicate enrichment in W (up to 424 mg/kg) and Mo (up to 24 mg/kg), similarly to the other neighboring mineralizations in western Milos (e.g. Vani, TriadesGalana). This enrichment suggests a magmatic-hydrothermal contribution to the ore fluids, probably from a buried granitoid at depth. Boiling, in addition to mixing processes between magmatic- and seawater, resulted in pH increase, oxidation and temperature decrease, and resulted into ore deposition.